Rutaecarpine ameliorates hyperlipidemia and hyperglycemia in fat-fed, streptozotocin-treated rats via regulating the IRS-1/PI3K/Akt and AMPK/ACC2 signaling pathways - Nie, Xu-qiang; Chen, Huai-hong; Zhang, Jian-yong; Zhang, Yu-jing; Yang, Jian-wen; Pan, Hui-jun; Song, Wen-xia; Murad, Ferid; He, Yu-qi; Bian, Ka (Acta pharmacologica Sinica, 2016)
Aim： We have shown that rutaecarpine extracted from the dried fruit of Chinese herb Evodia rutaecarpa （Juss） Benth （Wu Zhu Yu） promotes glucose consumption and anti-inflammatory cytokine expression in insulin-resistant primary skeletal muscle ceils. In this study we investigated whether rutaecarpine ameliorated the obesity profiles, lipid abnormality, glucose metabolism and insulin resistance in rat model of hyperlipidemia and hyperglycemia. Methods Rats fed on a high-fat diet for 8 weeks, followed by injection of streptozotocin （30 mg/kg, ip） to induce hyperlipidemia and hyperglycemia. One week after streptozotocin injection, the fat-fed, streptozotocin-treated rats were orally treated with rutaecarpine （25 mg-kg-1d-1） or a positive control drug metformin （250 mg.kg-1.d 1） for 7 weeks, The body weight, visceral fat, blood lipid profiles and glucose levels, insulin sensitivity were measured. Serum levels of inflammatory cytokines were analyzed. IRS-1 and Akt/PKB phosphorylation, PI3K and NF-KB protein levels in liver tissues were assessed; pathological changes of livers and pancreases were examined. Glucose uptake and AMPK/ACC2 phosphorylation were studied in cultured rat skeletal muscle cells in vitro. Results： Administration of rutaecarpine or metformin significantly decreased obesity, visceral fat accumulation, water consumption, and serum TC, TG and LDL-cholesterol levels in fat-fed, streptozotocin-treated rats. The two drugs also attenuated hyperglycemia and enhanced insulin sensitivity. Moreover, the two drugs significantly decreased NF-KB protein levels in liver tissues and plasma TNF-a, IL-6, CRP and MCP-1 levels, and ameliorated the pathological changes in livers and pancreases. In addition, the two drugs increased PI3K p85 subunit levels and Akt/PKB phosphorylation, but decreased iRS-1 phosphorylation in liver tissues. Treatment of cultured skeletal muscle cells with rutaecarpine （20-180 pmol/L） or metformin （20 pmol/L） promoted the phosphorylation of AMPK and ACC2 and increased glucose uptake. Conclusion： Rutaecarpine ameliorates hyperlipidemJa and hyperglycemia in fat-fed, streptozotocin-treated rats via regulating IRS-1/ PI3K/Akt signaling pathway in liver and AMPK/ACC2 signaling pathway in skeletal muscles.